Literature Review: The Effect of Kinesio Taping on Back Pain in Pregnant Women in Their Third Trimester - Solihah, Rosidah; Lestari, Lusi; Nurherliyany, Metty (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Back pain in pregnant women is one of the most common discomforts experienced by pregnant women. This back pain is typically felt by pregnant women during the third trimester of pregnancy, around 28–40 weeks of gestation. One approach to reducing back pain involves the use of kinesiotaping. Kinesiotaping is a new method of applying tape used to prevent and rehabilitate injuries. The objective of this study is to review literature, articles, and research documents on the management of back pain in pregnant women using kinesiotaping. Method: The method used is a literature review, involving the collection of data from the Google Scholar database from 2022 to 2025. The selected literature data were full-text journals in Indonesian. Result: Kinesio taping is a non-pharmacological method used to alleviate back pain in pregnant women. This therapy works by stabilizing joints, improving muscle function and position, and reducing pain receptor stimulation, thereby helping to reduce pain and strengthen abdominal muscles. Conclusion: Based on the literature review, kinesiotaping has been proven to be an effective non-pharmacological method for alleviating back pain in pregnant women, particularly in the third trimester. This therapy improves joint stability, enhances muscle function, and reduces pain receptor stimulation, thereby providing comfort and improving the quality of life for pregnant women.